Laser frequency conversion material, preparation method, printing ink and anti-counterfeiting coating
A stable, low-cost laser frequency conversion material addresses the limitations of existing anti-counterfeiting technologies by providing invisible detection and flexible application, enhancing security and reducing imitation risks.
Patent Information
- Application Number
- CN202411144334.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing anti-counterfeiting technologies are costly, complex, require special equipment, and have high imitation risks due to their technical complexity and visibility, lacking flexibility and stability.
A laser frequency conversion material composed of a phosphate-rare earth oxide complex, prepared by a solid phase method using diammonium phosphate, yttrium oxide, and erbium oxide, with controlled heating and calcination processes to ensure stable crystal morphology and low-cost production.
The material provides effective anti-counterfeiting performance with invisible detection frequency, low-cost production, and flexible application methods, ensuring reliable and quick identification with simple equipment.
Smart Images

Figure CN119118085A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new material preparation, and in particular to a laser frequency conversion material, a preparation method, ink and an anti-counterfeiting coating. Background Art
[0002] Anti-counterfeiting labels are not only beneficial to protecting consumer rights, but also can enhance the brand image of enterprises. With the continuous expansion of market demand, the requirements for anti-counterfeiting technology are getting higher and higher. Some low-cost anti-counterfeiting technologies used in existing anti-counterfeiting labels are very easy to be counterfeited and imitated due to their low threshold and high diffusion, such as color-changing anti-counterfeiting, telephone anti-counterfeiting, barcode anti-counterfeiting, laser anti-counterfeiting, etc. Some cutting-edge anti-counterfeiting technologies, such as plate-making anti-counterfeiting, information anti-counterfeiting, and security line anti-counterfeiting, are expensive because of their high technical content, high threshold for use, and long design cycle. In addition, the processes of these anti-counterfeiting technologies are generally complex and not flexible enough to use. There are also some anti-counterfeiting technologies, such as intelligent anti-counterfeiting and biological anti-counterfeiting, which require special high-precision equipment due to their complex identification technology and high cost of use.
[0003] Therefore, it is necessary to propose an anti-counterfeiting material and a preparation method which are low in cost, good in anti-counterfeiting performance and difficult to be imitated. Summary of the invention
[0004] The purpose of the present invention is to provide a laser frequency conversion material, a preparation method, ink and an anti-counterfeiting coating, which are used to solve the problems of uncontrollable morphology, poor stability and environmental pollution of laser frequency conversion materials in the existing preparation process.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] In a first aspect, the present invention provides a laser frequency conversion material, which is a phosphate-rare earth oxide complex prepared from diammonium phosphate, yttrium oxide, ytterbium oxide, and erbium oxide in a mass ratio of 10:9:2:0.1.
[0007] As a possible implementation method, the laser frequency conversion material is a structure in which yttrium oxide and ytterbium oxide are wrapped by erbium oxide and physically bonded with phosphate.
[0008] As a possible implementation, the shape of the phosphate-rare earth oxide mixture crystal is cubic.
[0009] In a second aspect, the present invention provides a method for preparing a laser frequency conversion material, which is prepared by a solid phase method and comprises the following steps:
[0010] S10. Weigh ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide, and erbium oxide in a mass ratio of 10:9:2:0.1 and mix them thoroughly;
[0011] S11. The mixture obtained in S10 is placed in a calcining furnace with an initial temperature of 25°C to 100°C, heated to 800°C at a heating rate of 30 to 40°C / min, and then kept warm for 1 hour; during the process, the diammonium phosphate is decomposed into phosphate and ammonia, and the impact force of the ammonia is used to fully mix the yttrium oxide, ytterbium oxide, erbium oxide and phosphate;
[0012] S12. The mixture obtained in S11 was cooled to room temperature in a calcining furnace and then taken out and pulverized to obtain a coarse powder;
[0013] S13. The coarse powder obtained in S12 is placed in a calcining furnace with an initial temperature of 25°C to 100°C, heated to 1300°C at a heating rate of 45 to 50°C / min, and then kept warm for 1 hour; during the process, the ammonium dihydrogen phosphate is decomposed into phosphate and ammonia, and the impact force of the ammonia is used to fully mix the yttrium oxide, ytterbium oxide and phosphate, and the erbium oxide is heated and melted to wrap the yttrium oxide and ytterbium oxide and then physically bonded to the phosphate;
[0014] S14. The coarse powder obtained in S13 is cooled to room temperature in a calcining furnace and then taken out and crushed to obtain a fine powder;
[0015] S15. Use a sieve with a preset mesh size to sieve the fine powder to obtain the laser frequency conversion material.
[0016] As a possible implementation method, S10 specifically includes the following steps:
[0017] S100. Calculate the amount of ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide, and erbium oxide according to the mass ratio of 10:9:2:0.1; weigh ammonium dihydrogen phosphate according to 105% of the amount; weigh the mass of yttrium oxide with an accuracy of not less than 1%; weigh the mass of ytterbium oxide and erbium oxide with an accuracy of not less than 1 / 1000;
[0018] S101. The weighed ammonium dihydrogen phosphate was crushed to less than 50 microns using a grinder, and the crushing time was controlled within 1 hour;
[0019] S102. Drying the four raw materials of ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide and erbium oxide;
[0020] S103. The ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide and erbium oxide obtained in S102 were placed in a stirrer and stirred at a stirring rate of 800 rpm to 1000 rpm for one hour;
[0021] S104. Drying the raw material obtained in step S103.
[0022] As a possible implementation, the placement order in S103 is 1 / 2 mass ammonium dihydrogen phosphate, 1 / 2 mass yttrium oxide, 1 / 2 mass ytterbium oxide, full mass erbium oxide, 1 / 2 mass ytterbium oxide, 1 / 2 mass ytterbium oxide, and 1 / 2 mass ammonium dihydrogen phosphate.
[0023] As a possible implementation, the crushing parameters in S12 and S14 include crushing frequency and crushing time. The crushing frequency is 5000R / min, and the crushing time is 30min.
[0024] As a possible implementation method, S15 specifically includes:
[0025] S150. Sieve the fine powder using a sieve of the first mesh number, and retain the fine powder having a particle size greater than the first mesh number;
[0026] S151. The fine powder retained by S150 is sieved using a second mesh sieve, and the fine powder with a particle size smaller than the second mesh is retained as a laser frequency conversion material, and the second mesh is smaller than the first mesh;
[0027] As a possible implementation, the particle size of the laser frequency conversion material is 50um to 300um.
[0028] In a third aspect, the present invention provides an anti-counterfeiting ink, the formula of the anti-counterfeiting ink being: 25 parts by mass of solvent, 1 part by mass of dispersing aid, 0.1 parts by mass of laser frequency conversion material, and 50 parts by mass of resin; the laser frequency conversion material is the laser frequency conversion material provided in the first aspect; or, the laser frequency conversion material is made using the preparation method of the laser frequency conversion material provided in the second aspect.
[0029] In a fourth aspect, the present invention provides an anti-counterfeiting coating, wherein the anti-counterfeiting ink provided in the third aspect is applied to the surface of a marker to obtain the anti-counterfeiting coating; the thickness of the anti-counterfeiting coating is 10 to 20 microns.
[0030] Compared with the prior art, the beneficial effects of the present invention are:
[0031] 1. The laser frequency conversion material provided by the present invention can be obtained by using only four raw materials, has a simple formula, uses less materials, and has low cost. The material is a white powder without coloring ability. The anti-counterfeiting ink made from it has good concealment and is not easy to be discovered. The working frequency band of the material detection instrument is invisible light, and the frequency band is confidential, which is not easy to be cracked and imitated.
[0032] 2. The laser frequency conversion material provided by the present invention can be used in ink materials for printing, can be added to coatings for spraying, can also be used in injection molded parts or formed separately, and the application methods are flexible, varied, simple and convenient.
[0033] 3. The laser frequency conversion material provided by the present invention has a stable production process, good material reproducibility, and a long material service life, which can ensure the reliability of the anti-counterfeiting function. The identification equipment of this material has a low cost, is simple and quick to operate, and has excellent anti-counterfeiting performance.
[0034] 4. The preparation method of the laser frequency conversion material provided by the present invention, the raw materials are subjected to two high-temperature calcinations. By controlling the heating rate and the insulation temperature, the decomposition rate of the gas in the diammonium phosphate can be effectively avoided to be too fast or too slow, so that the finally obtained laser frequency conversion material has a stable crystal morphology and a better preparation effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0036] Figure 1 This is a graph showing the absorption spectrum of the laser frequency conversion material in an embodiment of the present invention;
[0037] Figure 2 The XRD spectrum of the laser frequency conversion material in the embodiment of the present invention;
[0038] Figure 3 This is a scanning electron microscope image of the laser frequency conversion material in an embodiment of the present invention;
[0039] Figure 4 This is a flow chart of a method for preparing a laser frequency conversion material according to an embodiment of the present invention;
[0040] Figure 5 This is an excitation spectrum curve of the laser frequency conversion material in an embodiment of the present invention. DETAILED DESCRIPTION
[0041] In order to clearly describe the technical solutions of the embodiments of the present invention, in the embodiments of the present invention, words such as "first" and "second" are used to distinguish the same items or similar items with basically the same functions and effects. For example, the first threshold and the second threshold are only used to distinguish different thresholds, and their order is not limited. Those skilled in the art can understand that words such as "first" and "second" do not limit the quantity and execution order, and words such as "first" and "second" do not necessarily limit them to be different.
[0042] It should be noted that, in the present invention, words such as "exemplary" or "for example" are used to indicate examples, illustrations or descriptions. Any embodiment or design described as "exemplary" or "for example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of words such as "exemplary" or "for example" is intended to present related concepts in a specific way.
[0043] In the present invention, "at least one" means one or more, and "plurality" means two or more. "And / or" describes the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone, where A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship. The following at least one item (items) or similar expressions thereof refer to any combination of these items, including any combination of single items (items) or plural items (items). For example, at least one item (items) of a, b or c can mean: a, b, c, the combination of a and b, the combination of a and c, the combination of b and c, or the combination of a, b and c, where a, b, c can be single or multiple.
[0044] In a first aspect, the present invention provides a laser frequency conversion material, which is a phosphate-rare earth oxide complex prepared from diammonium phosphate, yttrium oxide, ytterbium oxide, and erbium oxide in a mass ratio of 10:9:2:0.1.
[0045] See also Figure 1 The laser frequency conversion material has the ability to convert near-infrared laser frequency conversion, which can absorb the light in the 980nm band and convert it into the excitation light in the 1550nm band, so that it can be sensed and recognized by the identifier. Figure 2 , which is the XRD spectrum of the laser frequency conversion material provided by the present invention. Therefore, the laser frequency conversion material provided by the present invention can be used to make anti-counterfeiting ink, which has low cost, simple operation and good concealment.
[0046] As a possible implementation method, the laser frequency conversion material is a structure in which yttrium oxide and ytterbium oxide are wrapped by erbium oxide and physically bonded with phosphate.
[0047] As a possible implementation method, the shape of the phosphate-rare earth oxide mixture crystal is cubic. Figure 3 , is a scanning electron microscope image of the laser frequency conversion material of the present invention, from which it can be seen that the crystal particles are aggregated and accumulated, and have good stability.
[0048] In a second aspect, the present invention provides a method for preparing a laser frequency conversion material, which is prepared by a solid phase method, see Figure 4 , including the following steps:
[0049] S10. Weigh ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide, and erbium oxide in a mass ratio of 10:9:2:0.1 and mix them thoroughly;
[0050] As a possible implementation method, S10 specifically includes the following steps:
[0051] S100. Calculate the amount of ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide, and erbium oxide according to the mass ratio of 10:9:2:0.1; weigh ammonium dihydrogen phosphate according to 105% of the amount; weigh the mass of yttrium oxide with an accuracy of not less than 1%; weigh the mass of ytterbium oxide and erbium oxide with an accuracy of not less than 1 / 1000;
[0052] S101. The weighed ammonium dihydrogen phosphate is crushed to less than 50 microns using a grinder, and the crushing time is controlled within 1 hour to prevent the material from absorbing moisture;
[0053] S102. Drying the four raw materials of ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide and erbium oxide;
[0054] As an example, four raw materials, namely, ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide, and erbium oxide, are placed in a forced air oven and dried at 80° C. for 10 hours to remove moisture from the raw materials.
[0055] S103. The ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide and erbium oxide obtained in S102 were placed in a stirrer and stirred at a stirring rate of 800 rpm to 1000 rpm for one hour;
[0056] As an example, the stirring rates are: 800 rpm, 850 rpm, 900 rpm, 950 rpm, 1000 rpm.
[0057] As a possible implementation, the placement order in S103 is 1 / 2 mass ammonium dihydrogen phosphate, 1 / 2 mass yttrium oxide, 1 / 2 mass ytterbium oxide, full mass erbium oxide, 1 / 2 mass ytterbium oxide, 1 / 2 mass ytterbium oxide, and 1 / 2 mass ammonium dihydrogen phosphate.
[0058] S104. Drying the raw material obtained in step S103.
[0059] As an example, the drying method is: placing the raw material obtained in step S103 in a blast oven and drying it at 80° C. for 3 hours.
[0060] S11. The mixture obtained in S10 is placed in a calcining furnace with an initial temperature of 25°C to 100°C, heated to 800°C at a heating rate of 30 to 40°C / min, and then kept warm for 1 hour; during the process, the diammonium phosphate decomposes into phosphate ester and ammonia, and the impact force of the ammonia is used to fully mix the yttrium oxide, ytterbium oxide, erbium oxide and phosphate ester.
[0061] As an example, the calcination furnace uses a muffle furnace with initial temperatures of 25°C, 35°C, 45°C, 55°C, 65°C, 75°C, 80°C, 90°C, and 100°C, and heating rates of 30°C / min, 32°C / min, 34°C / min, 36°C / min, 38°C / min, and 40°C / min.
[0062] S12. The mixture obtained in S11 was cooled to room temperature in a calcining furnace and then taken out and pulverized to obtain a coarse powder;
[0063] As an example, the mixture obtained in S11 is cooled to room temperature in the calcining furnace, taken out, and put into a pulverizer for pulverization at a pulverization frequency of 5000 R / min and a pulverization time of 30 min to obtain a coarse powder.
[0064] S13. The coarse powder obtained in S12 is placed in a calcining furnace with an initial temperature of 25°C to 100°C, heated to 1300°C at a heating rate of 45 to 50°C / min, and then kept warm for 1 hour; during the process, the ammonium dihydrogen phosphate is decomposed into phosphate and ammonia, and the impact force of the ammonia is used to fully mix the yttrium oxide, ytterbium oxide and phosphate, and the erbium oxide is heated and melted to wrap the yttrium oxide and ytterbium oxide and then physically bonded to the phosphate;
[0065] As an example, the calcination furnace uses a muffle furnace with initial temperatures of 25°C, 35°C, 45°C, 55°C, 65°C, 75°C, 80°C, 90°C, and 100°C, and heating rates of 45°C / min, 46°C / min, 47°C / min, 48°C / min, 49°C / min, and 50°C / min.
[0066] This method uses two calcinations to control the heating rate within a certain range. If the heating rate is too low, the decomposition will produce gas slowly and the impact will be weak, and the powder will easily form large lumps, affecting the final crystal shape of the powder; if the heating rate is too high, the decomposition will produce gas quickly and the impact will be strong, and the gas impact cannot be maintained throughout the process, causing the powder to easily form large lumps, and the rare earth oxides and the decomposition products of diammonium phosphate cannot be fully combined to form a phosphoric acid-rare earth oxide complex, resulting in a decrease in yield. This method can promote the decomposition of diammonium phosphate into phosphate and ammonia, and under the action of gas, the material mixing and doping are more sufficient and uniform, and the preparation effect is better.
[0067] S14. The coarse powder obtained in S13 is cooled to room temperature in a calcining furnace and then taken out and crushed to obtain a fine powder;
[0068] As an example, the mixture obtained in S13 is cooled to room temperature in the calcining furnace, taken out, and put into a pulverizer for pulverization at a pulverization frequency of 5000 R / min and a pulverization time of 30 min to obtain a coarse powder.
[0069] S15. Use a sieve with a preset mesh size to sieve the fine powder to obtain the laser frequency conversion material.
[0070] As a possible implementation method, S15 specifically includes:
[0071] S150. Sieve the fine powder using a sieve of the first mesh number, and retain the fine powder having a particle size greater than the first mesh number;
[0072] As an example, the sieve with the first mesh number is an 8000-mesh sieve, and after the fine powder is sieved, the fine powder with a particle size greater than 8000 mesh is retained.
[0073] S151. The fine powder retained by S150 is sieved using a second mesh sieve, and the fine powder with a particle size smaller than the second mesh is retained as a laser frequency conversion material, and the second mesh is smaller than the first mesh;
[0074] As an example, the second mesh size sieve is a 50-mesh sieve, and after the fine powder retained by sieving S150, the fine powder with a particle size less than 50 mesh is retained to obtain the laser frequency conversion material.
[0075] As a possible implementation manner, the particle size of the laser frequency conversion material is 50um to 300um, for example, 50um, 100um, 150um, 200um, 250um, 300um.
[0076] In a third aspect, the present invention provides an anti-counterfeiting ink, the formula of the anti-counterfeiting ink being: 25 parts by mass of solvent, 1 part by mass of dispersing aid, 0.1 parts by mass of laser frequency conversion material, and 50 parts by mass of resin; the laser frequency conversion material is the laser frequency conversion material provided in the first aspect; or, the laser frequency conversion material is made using the preparation method of the laser frequency conversion material provided in the second aspect.
[0077] For example, the solvent is a mixture of ethyl acetate and butyl acetate in a mass ratio of 1:1, and the resin may be acrylic resin, polyurethane resin, or other common room temperature curing ink resins for labels.
[0078] In a fourth aspect, the present invention provides an anti-counterfeiting coating, wherein the anti-counterfeiting ink provided in the third aspect is applied to the surface of a marker to obtain the anti-counterfeiting coating; the thickness of the anti-counterfeiting coating is 10 to 20 microns.
[0079] To facilitate understanding of the technical solution of the present application, further explanation is provided below in conjunction with specific embodiments and comparative examples.
[0080] Example 1
[0081] 1. Weigh the raw materials according to the mass ratio of 100.00g of diammonium phosphate, 9.00g of yttrium oxide, 2.00g of ytterbium oxide, and 0.1000g of erbium oxide, among which 5.00g of diammonium phosphate is additionally weighed;
[0082] 2. Use a grinder to grind the weighed ammonium dihydrogen phosphate to less than 50 microns;
[0083] 3. Place 1 / 2 mass of ammonium dihydrogen phosphate, 1 / 2 mass of yttrium oxide, 1 / 2 mass of ytterbium oxide, the whole mass of erbium oxide, 1 / 2 mass of ytterbium oxide, 1 / 2 mass of ytterbium oxide, and 1 / 2 mass of ammonium dihydrogen phosphate into the stirrer in sequence, and stir at a stirring rate of 800 rpm for 1 hour;
[0084] 4. After stirring, place the mixed raw materials in a blast oven and dry them at 80°C for 3 hours;
[0085] 5. Place the dried mixture in a muffle furnace with an initial temperature of 25°C, heat to 800°C at a heating rate of 30°C / min, and keep it at that temperature for 1 hour;
[0086] 6. After the mixture is cooled to room temperature in the muffle furnace, it is taken out and put into a pulverizer at a frequency of 5000 R / min for 30 minutes;
[0087] 7. Place the coarse powder obtained by crushing in a muffle furnace with an initial temperature of 25°C, heat to 1300°C at a heating rate of 45°C / min, and keep it at this temperature for 1 hour;
[0088] 8. Cool the coarse powder to room temperature in the muffle furnace, take it out, put it into a pulverizer at a frequency of 5000R / min and pulverize it for 30 minutes;
[0089] 9. Use an 8000 mesh screen to sieve the crushed powder, and use a 50 mesh screen to sieve the powder remaining on the screen. Take the sieved powder for particle size test, and the particle size between 50um and 300um is qualified laser frequency conversion material.
[0090] 10. Take 1g of laser frequency conversion material and add it to 250g of solvent at a stirring rate of 1000rmp. The solvent is 50% ethyl acetate and 50% butyl acetate. Then add 10g of dispersing aid and 500g of acrylic resin (solid content 80%) in sequence at the same stirring rate. After the addition is completed, maintain the stirring rate of 1000rmp for 30 minutes to obtain anti-counterfeiting ink.
[0091] 11. Spray the anti-counterfeiting ink on the identification mark with a spray thickness of 10um and spray parameters: spray gun caliber 1.5mm, spray gun distance 250mm, moving speed 0.2m / s, spray gun pressure 0.8MPa, spraying times 1 time. After spraying, solidify at room temperature to obtain an anti-counterfeiting coating.
[0092] Example 2
[0093] 1. Weigh the raw materials according to the mass ratio of 100.00g of diammonium phosphate, 9.00g of yttrium oxide, 2.00g of ytterbium oxide, and 0.1000g of erbium oxide, among which 5.00g of diammonium phosphate is additionally weighed;
[0094] 2. Use a grinder to grind the weighed ammonium dihydrogen phosphate to less than 50 microns;
[0095] 3. Place 1 / 2 mass of ammonium dihydrogen phosphate, 1 / 2 mass of yttrium oxide, 1 / 2 mass of ytterbium oxide, the whole mass of erbium oxide, 1 / 2 mass of ytterbium oxide, 1 / 2 mass of ytterbium oxide, and 1 / 2 mass of ammonium dihydrogen phosphate into the stirrer in sequence, and stir at a stirring rate of 800 rpm for 1 hour;
[0096] 4. After stirring, place the mixed raw materials in a blast oven and dry them at 80°C for 3 hours;
[0097] 5. Place the dried mixture in a muffle furnace with an initial temperature of 25°C, heat to 800°C at a heating rate of 40°C / min, and keep it at that temperature for 1 hour;
[0098] 6. After the mixture is cooled to room temperature in the muffle furnace, it is taken out and put into a pulverizer at a frequency of 5000 R / min for 30 minutes;
[0099] 7. Place the coarse powder obtained by crushing in a muffle furnace with an initial temperature of 25°C, heat to 1300°C at a heating rate of 50°C / min, and keep it at this temperature for 1 hour;
[0100] 8. Cool the coarse powder to room temperature in the muffle furnace, take it out, put it into a pulverizer at a frequency of 5000R / min and pulverize it for 30 minutes;
[0101] 9. Use an 8000 mesh screen to sieve the crushed powder, and use a 50 mesh screen to sieve the powder remaining on the screen. Take the sieved powder for particle size test, and the particle size between 50um and 300um is qualified laser frequency conversion material.
[0102] 10. Take 1g of laser frequency conversion material and add it to 250g of solvent at a stirring rate of 1000rmp. The solvent is 50% ethyl acetate and 50% butyl acetate. Then add 10g of dispersing aid and 500g of acrylic resin (solid content 80%) in sequence at the same stirring rate. After the addition is completed, maintain the stirring rate of 1000rmp for 30 minutes to obtain anti-counterfeiting ink.
[0103] 11. Spray the anti-counterfeiting ink on the identification mark with a spray thickness of 10um and spray parameters: spray gun caliber 1.5mm, spray gun distance 250mm, moving speed 0.2m / s, spray gun pressure 0.8MPa, spraying times 1 time. After spraying, solidify at room temperature to obtain an anti-counterfeiting coating.
[0104] Example 3
[0105] 1. Weigh the raw materials according to the mass ratio of 100.00g of diammonium phosphate, 9.00g of yttrium oxide, 2.00g of ytterbium oxide, and 0.1000g of erbium oxide, among which 5.00g of diammonium phosphate is additionally weighed;
[0106] 2. Use a grinder to grind the weighed ammonium dihydrogen phosphate to less than 50 microns;
[0107] 3. Place 1 / 2 mass of ammonium dihydrogen phosphate, 1 / 2 mass of yttrium oxide, 1 / 2 mass of ytterbium oxide, the whole mass of erbium oxide, 1 / 2 mass of ytterbium oxide, 1 / 2 mass of ytterbium oxide, and 1 / 2 mass of ammonium dihydrogen phosphate into the stirrer in sequence, and stir at a stirring rate of 800 rpm for 1 hour;
[0108] 4. After stirring, place the mixed raw materials in a blast oven and dry them at 80°C for 3 hours;
[0109] 5. Place the dried mixture in a muffle furnace with an initial temperature of 25°C, heat to 800°C at a heating rate of 35°C / min, and keep it at that temperature for 1 hour;
[0110] 6. After the mixture is cooled to room temperature in the muffle furnace, it is taken out and put into a pulverizer at a frequency of 5000 R / min for 30 minutes;
[0111] 7. Place the coarse powder obtained by crushing in a muffle furnace with an initial temperature of 25°C, heat to 1300°C at a heating rate of 47°C / min, and keep it at this temperature for 1 hour;
[0112] 8. Cool the coarse powder to room temperature in the muffle furnace, take it out, put it into a pulverizer at a frequency of 5000R / min and pulverize it for 30 minutes;
[0113] 9. Use an 8000 mesh screen to sieve the crushed powder, and use a 50 mesh screen to sieve the powder remaining on the screen. Take the sieved powder for particle size test, and the particle size between 50um and 300um is qualified laser frequency conversion material.
[0114] 10. Take 1g of laser frequency conversion material and add it to 250g of solvent at a stirring rate of 1000rmp. The solvent is 50% ethyl acetate and 50% butyl acetate. Then add 10g of dispersing aid and 500g of acrylic resin (solid content 80%) in sequence at the same stirring rate. After the addition is completed, maintain the stirring rate of 1000rmp for 30 minutes to obtain anti-counterfeiting ink.
[0115] 11. Spray the anti-counterfeiting ink on the identification mark with a spray thickness of 10um and spray parameters: spray gun caliber 1.5mm, spray gun distance 250mm, moving speed 0.2m / s, spray gun pressure 0.8MPa, spraying times 1 time. After spraying, solidify at room temperature to obtain an anti-counterfeiting coating.
[0116] Comparative Example
[0117] 1. Weigh the raw materials according to the mass ratio of 100.00g of diammonium phosphate, 9.00g of yttrium oxide, 2.00g of ytterbium oxide, and 0.1000g of erbium oxide, among which 5.00g of diammonium phosphate is additionally weighed;
[0118] 2. Use a grinder to grind the weighed ammonium dihydrogen phosphate to less than 50 microns;
[0119] 3. Place 1 / 2 mass of ammonium dihydrogen phosphate, 1 / 2 mass of yttrium oxide, 1 / 2 mass of ytterbium oxide, the whole mass of erbium oxide, 1 / 2 mass of ytterbium oxide, 1 / 2 mass of ytterbium oxide, and 1 / 2 mass of ammonium dihydrogen phosphate into the stirrer in sequence, and stir at a stirring rate of 800 rpm for 1 hour;
[0120] 4. After stirring, place the mixed raw materials in a blast oven and dry them at 80°C for 3 hours;
[0121] 5. Place the dried mixture in a muffle furnace with an initial temperature of 20°C, heat to 800°C at a heating rate of 20°C / min, and keep warm for 1 hour;
[0122] 6. After the mixture is cooled to room temperature in the muffle furnace, it is taken out and put into a pulverizer at a frequency of 5000 R / min for 30 minutes;
[0123] 7. Place the coarse powder obtained by crushing in a muffle furnace with an initial temperature of 25°C, heat to 800°C at a heating rate of 50°C / min, and keep it at this temperature for 1 hour;
[0124] 8. Cool the coarse powder to room temperature in the muffle furnace, take it out, put it into a pulverizer at a frequency of 5000R / min and pulverize it for 30 minutes;
[0125] 9. Use an 8000 mesh screen to sieve the crushed powder, and use a 50 mesh screen to sieve the powder remaining on the screen. Take the sieved powder for particle size test, and the particle size between 50um and 300um is qualified laser frequency conversion material.
[0126] 10. Take 1g of laser frequency conversion material and add it to 250g of solvent at a stirring rate of 1000rmp. The solvent is 50% ethyl acetate and 50% butyl acetate. Then add 10g of dispersing aid and 500g of acrylic resin (solid content 80%) in sequence at the same stirring rate. After the addition is completed, maintain the stirring rate of 1000rmp for 30 minutes to obtain anti-counterfeiting ink.
[0127] 11. Spray the anti-counterfeiting ink on the identification mark with a spray thickness of 10um and spray parameters: spray gun caliber 1.5mm, spray gun distance 250mm, moving speed 0.2m / s, spray gun pressure 0.8MPa, spraying times 1 time. After spraying, solidify at room temperature to obtain an anti-counterfeiting coating.
[0128] Compared with Example 1, Example 2 and Example 3, the comparative example reduces the first heating rate and the temperature to be reached in the second calcination. Figure 5 It can be seen that the anti-counterfeiting inks obtained in Example 1, Example 2, and Example 3 have significant frequency conversion characteristics near 1550nm and are easy to identify; while the anti-counterfeiting ink obtained in the comparative example has insignificant frequency conversion characteristics near 1550nm and is not easy to identify. Further experiments show that the anti-counterfeiting coatings obtained in Example 1, Example 2, and Example 3 can all be identified by the identifier, causing the identifier to vibrate, while the anti-counterfeiting coatings obtained in the comparative example cannot cause the identifier to vibrate. Therefore, the anti-counterfeiting coating of the present invention is low-cost and easy to identify, and the working frequency band of the detection instrument is invisible light, and the frequency band is confidential and not easy to be cracked and imitated.
[0129] Although the present invention is described herein in conjunction with various embodiments, in the process of implementing the claimed invention, those skilled in the art may understand and implement other variations of the disclosed embodiments by viewing the drawings, the disclosure, and the drawings, etc. In the specification, the word "comprising" does not exclude other components or steps, and "one" or "an" does not exclude multiple situations. A single processor or other unit can implement several functions listed in the specification. Certain measures are recorded in different embodiments, but this does not mean that these measures cannot be combined to produce good results.
[0130] Although the present invention has been described in conjunction with specific features and embodiments thereof, it is apparent that various modifications and combinations may be made thereto without departing from the spirit and scope of the present invention. Accordingly, this specification and the accompanying drawings are merely exemplary illustrations of the present invention and are deemed to cover any and all modifications, variations, combinations or equivalents within the scope of the present invention. Obviously, those skilled in the art may make various modifications and variations to the present invention without departing from the spirit and scope of the present invention. Thus, the present invention is intended to include such modifications and variations if they fall within the scope of the present invention and its equivalents.
Claims
1. A laser frequency conversion material, characterized in that: The laser frequency conversion material is a phosphate-rare earth oxide complex prepared from ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide and erbium oxide in a mass ratio of 10:9:2:0.
1.
2. The laser frequency conversion material according to claim 1, characterized in that: The laser frequency conversion material is a structure in which yttrium oxide and ytterbium oxide are wrapped by erbium oxide and then physically bonded with phosphate.
3. The laser frequency conversion material according to claim 1, characterized in that: The shape of the phosphate-rare earth oxide mixture crystal is cubic.
4. A method for preparing a laser frequency conversion material, characterized in that: The solid phase method is used for preparation, comprising the following steps: S10. Weigh ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide, and erbium oxide in a mass ratio of 10:9:2:0.1 and mix them thoroughly; S11. The mixture obtained in S10 is placed in a calcining furnace with an initial temperature of 25°C to 100°C, heated to 800°C at a heating rate of 30 to 40°C / min, and then kept warm for 1 hour; during the process, the diammonium phosphate is decomposed into phosphate and ammonia, and the impact force of the ammonia is used to fully mix the yttrium oxide, ytterbium oxide, erbium oxide and phosphate; S12. The mixture obtained in S11 was cooled to room temperature in a calcining furnace and then taken out and pulverized to obtain a coarse powder; S13. The coarse powder obtained in S12 is placed in a calcining furnace with an initial temperature of 25°C to 100°C, heated to 1300°C at a heating rate of 45 to 50°C / min, and then kept warm for 1 hour; during the process, the ammonium dihydrogen phosphate is decomposed into phosphate and ammonia, and the impact force of the ammonia is used to fully mix the yttrium oxide, ytterbium oxide and phosphate, and the erbium oxide is heated and melted to wrap the yttrium oxide and ytterbium oxide and then physically bonded to the phosphate; S14. The coarse powder obtained in S13 is cooled to room temperature in a calcining furnace and then taken out and crushed to obtain a fine powder; S15. Use a sieve with a preset mesh size to sieve the fine powder to obtain the laser frequency conversion material.
5. The method for preparing the laser frequency conversion material according to claim 4, characterized in that: The S10 specifically includes the following steps: S100. Calculate the amount of ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide, and erbium oxide according to the mass ratio of 10:9:2:0.1; weigh ammonium dihydrogen phosphate according to 105% of the amount; weigh the mass of yttrium oxide with an accuracy of not less than 1%; weigh the mass of ytterbium oxide and erbium oxide with an accuracy of not less than 1 / 1000; S101. The weighed ammonium dihydrogen phosphate was crushed to less than 50 microns using a grinder, and the crushing time was controlled within 1 hour; S102. Drying the four raw materials of ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide and erbium oxide; S103. The ammonium dihydrogen phosphate, yttrium oxide, ytterbium oxide and erbium oxide obtained in S102 were placed in a stirrer and stirred at a stirring rate of 800 rpm to 1000 rpm for one hour; S104. Drying the raw material obtained in step S103.
6. The method for preparing the laser frequency conversion material according to claim 5, characterized in that: The placement order in S103 is 1 / 2 mass ammonium dihydrogen phosphate, 1 / 2 mass yttrium oxide, 1 / 2 mass ytterbium oxide, full mass erbium oxide, 1 / 2 mass ytterbium oxide, 1 / 2 mass yttrium oxide, and 1 / 2 mass ammonium dihydrogen phosphate.
7. The method for preparing the laser frequency conversion material according to claim 4, characterized in that: The crushing parameters in S12 and S14 include crushing frequency and crushing time. The crushing frequency is 5000R / min, and the crushing time is 30min.
8. The method for preparing the laser frequency conversion material according to claim 4, characterized in that: The S15 specifically includes: S150. Sieve the fine powder using a sieve of the first mesh number, and retain the fine powder having a particle size greater than the first mesh number; S151. The fine powder retained by S150 is sieved using a second mesh screen, and the fine powder with a particle size smaller than the second mesh is retained as a laser frequency conversion material, and the second mesh is smaller than the first mesh; and / or, The particle size of the laser frequency conversion material is 50um to 300um.
9. An anti-counterfeiting ink, characterized in that: The formula of the anti-counterfeiting ink is: 25 parts by mass of solvent, 1 part by mass of dispersing aid, 0.1 parts by mass of laser frequency conversion material, and 50 parts by mass of resin; the laser frequency conversion material is the laser frequency conversion material described in any one of claims 1 to 3; or, the laser frequency conversion material is made by the preparation method of the laser frequency conversion material described in any one of claims 4 to 8.
10. An anti-counterfeiting coating, characterized in that: The anti-counterfeiting ink according to claim 9 is applied to the surface of the marking object to obtain the anti-counterfeiting coating; the thickness of the anti-counterfeiting coating is 10 to 20 microns.
Citation Information
Patent Citations
Phosphate based red phosphor, preparation method and application thereof
CN103320131A
Tantalate-based up-conversion luminescence material and preparation method thereof
CN104710987A
Tungstate upconversion luminescence temperature sensitive material doped with rare-earth elements Er and Yb and preparation method thereof
CN105131950A
Ultraviolet-to-blue light excited phosphate-based red fluorescent powder and preparation method thereof
CN105349147A
Inorganic powdery reversible photochromic material as well as preparation method and application
CN106833603A
